ANALISIS AKUNTABILITAS DAN TRANSPARANSI DALAM PENGELOLAAN DANA BANTUAN OPERASIONAL SATUAN PENDIDIKAN (BOSP) DI SD NEGERI 270 LEBANI KECAMATAN BELOPA UTARA KABUPATEN LUWU - Nuryanti, Nuryanti; Ilyas, Ilyas; Burhanuddin, Burhanuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the principles of accountability and transparency in the management of BOSP Funds at SD Negeri 270 Lebani which is reviewed from the aspects of planning, implementation, accountability, information disclosure, information accessibility, and stakeholder involvement, identifying factors that influence the implementation of the principles of accountability and transparency in the management of BOS funds at SD Negeri 270 Lebani. This study uses a qualitative approach with a descriptive method with data collection techniques carried out through observation, interviews, and documentation studies involving the principal, BOSP Fund treasurer, teachers, school committee, BOSP management team. The results of the study indicate that the competence of BOSP Fund managers, coordination between school personnel, implementation commitment, and leadership of the principal are internal factors that influence the implementation of accountability and transparency in the management of BOSP Funds, and government regulations, school committee supervision, community participation, and guidance from the education office are external factors that influence the management of BOSP Funds. Accountability is reflected through the preparation of a participatory RKAS, implementation of activities that refer to planning, and the preparation of accountability reports supported by complete administrative documents.